Improved algorithm for secure outsourcing of modular exponentiations with high checkability. (2016) - Ye, Jun; Chen, Xiaofeng; Ma, Jianfeng
With the development of cloud computing, outsourcing computation becomes a hot issue recently. Outsourcing computation allows a resource-constrained client to outsource the complicated computing tasks to a cloud server which is powerful but not honest. Modular exponentiation with a large modulus, which is considered as the most expensive operation in discrete logarithm based cryptographic protocols, has been widely used in public key cryptosystems for secure data communications. In this paper we put forth a new improved outsourcing algorithm for secure outsourcing of modular exponentiations. In the proposed algorithm, the modular exponentiations need to be computed are hidden to the malicious server. In the computation procedure, the server cannot obtain any information with respect to the input and output while the client can verify the returned result efficiently. Compared with the algorithms of Hohenberger and Lysyanskaya (2005) and Chen et al. (2012), ours are superior in checkability. In addition, the proposed algorithm can promote the efficiency of all security protocols based on discrete logarithm.